Preparation and studies of polyacrylonitrile ion conducting polymer electrolytes - Osman, Z.; Md. Isa, K.B.; Ahmad, A. (2009)
Polymer electrolyte systems composed of polyacrylonitrile (PAN) as the host polymer, ethylene carbonate (EC) and propylene carbonate (PC) as the plasticizers and LiCF3S03 as the doping salt were prepared by the solution casting technique. In this work, five systems of polymer electrolyte films have been prepared. They are; the (PAN+EC) system, the (PAN+PC) system, the (PAN+LiCF3S03) system, the (PAN+EC+LiCF3S03) and the (PAN+PC+LiCF3S03) system. The pure PAN film was prepared as a reference. The ionic conductivity for each system was obtained by calculation using data from impedance spectroscopy. The room temperature conductivity of the pure PAN film is 1.51 x 10-11 Scm-I. The room temperature conductivity for the highest conducting film in the (PAN+LiCF3S03) system is 3.04 x 10-4 Scm-I. On addition of plasticizers, the room temperature conductivity of (PAN+LiCF3S03) film increases. The conductivitytemperature studies are then performed on the highest conducting film from the (PAN+LiCF3S03) system, the (PAN+EC+LiCF3S03) system and the (PAN+PC+LiCF3S03) system. The conductivity-temperature studies are conducted in the temperature range between 303 K and 373 K. XRD studies shown that the complexation has occurred in PAN films containing lithium salt and plasticizers and complexes formed are amorphous. The FTIR results confirmed the complexation has taken place between PAN and the lithium salt.